2014
DOI: 10.1007/s11707-014-0479-y
|View full text |Cite
|
Sign up to set email alerts
|

Polarization signature from the FengYun-3 Microwave Humidity Sounder

Abstract: Microwave Humidity Sounders (MHS) onboard , and EUMETSAT MetOp-A/B satellites provide radiance measurements at a single polarization state at any of five observed frequencies. The Microwave Humidity Sounder (MWHS) onboard the FengYun-3 (FY-3) satellite has a unique instrument design that provides dual polarization measurements at 150 GHz. In this study, the MWHS polarization signal was investigated using observed and modeled data. It is shown that the quasi-polarization brightness temperatures at 150 GHz displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These channels can give information near the Earth's surface and lower atmosphere, and can also be used to measure atmospheric cloud parameters. For the 150 GHz channels, Zou et al (2014) investigated the polarization information and concluded that the polarization signal is related to the scanning angle and also to information such as surface wind speed, wind direction and salinity, especially in the clear-sky condition. The three channels around the 183.31GHz absorption line aim to get profiles of atmospheric humidity.…”
Section: Fy-3b/mwhsmentioning
confidence: 99%
“…These channels can give information near the Earth's surface and lower atmosphere, and can also be used to measure atmospheric cloud parameters. For the 150 GHz channels, Zou et al (2014) investigated the polarization information and concluded that the polarization signal is related to the scanning angle and also to information such as surface wind speed, wind direction and salinity, especially in the clear-sky condition. The three channels around the 183.31GHz absorption line aim to get profiles of atmospheric humidity.…”
Section: Fy-3b/mwhsmentioning
confidence: 99%
“…These channels can provide information near the Earth's surface and lower atmosphere and can also be used to measure atmospheric cloud parameters. For the 150 GHz channels, Zou et al (2014) investigated the polarization information and concluded that the polarization signal is related to the scan angle and information such as surface wind speed and wind direction and can also be strongly scattered by non-spherical ice cloud particles. Under all weather conditions, except heavy precipitation, all five channels of MWHS can observe water vapour and ice clouds in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%